Long-term analysis of PM2.5 from 2004 to 2017 in Toronto: Composition, sources, and oxidative potential. (August 2020) - Jeong, Cheol-Heon; Traub, Alison; Huang, Angela; Hilker, Nathan; Wang, Jonathan M.; Herod, Dennis; Dabek-Zlotorzynska, Ewa; Celo, Valbona; Evans, Greg J.
Abstract: Long-term trends (2004–2017) in the chemical composition and sources of PM2.5 (particulate matter smaller than 2.5 μm in diameter) in a metropolitan area were investigated using daily integrated PM2.5 chemical speciation data and continuous air pollution measurements. Eleven source factors were identified: coal combustion characterized by secondary sulphate, secondary nitrate, summertime organic carbon (OC), regional elemental carbon (EC), biomass burning, oil combustion, primary tailpipe emissions, non-tailpipe emissions related to road dust, non-tailpipe emissions related to brake wear, metal production, and road salt. Overall, coal combustion, secondary nitrate, regional EC, and oil combustion underwent marked decreases in concentrations with large reduction rates ranging from −8% yr −1 to −18% yr −1, contributing to an overall 34% decrease in annual PM2.5 over the past 14 years. Decreases in local tailpipe emissions (−3% yr −1 ) were consistent with the reduction of traffic-related air pollutants. In contrast, non-tailpipe emissions remained constant until 2010–2011 and then increased with a range of rates of 21% yr −1 to 27% yr −1 from 2011 to 2016. The contribution of summertime OC increased to approximately 27% in the summer of 2013–2016, rising to become the largest PM2.5 source driven by the reduction of regional sources. The chemical composition of PM2.5 in the urban area drastically changed from inorganic-rich to organic- and metal-rich particles during 2013–2016. The depletion of ascorbic acid was measured using filter samples collected over one year to identify PM2.5 components and sources contributing to the oxidative potential (OP) of PM2.5 . The OP was clearly associated with trace elements (e.g., Ba, Cu, Fe). Non-tailpipe emissions related to road dust and brake wear presented high redox activity per mass of PM2.5 . This work suggests that summertime OC and non-tailpipe emissions in recent years have become increasingly important. As such, policies targeting traffic-related PM2.5 should focus on these sources for maximum impact. Graphical abstract: Image 1 Highlights: Long-term trends of PM2.5 sources were identified during the period 2004–2017. PM2.5 decreased by 34% mainly due to reduced emissions from coal-fired power plants. A change in the chemical composition of PM2.5 to organic- and metal-rich was found. Non-tailpipe emissions are rising, whereas primary tailpipe emissions drop. Non-tailpipe PM2.5 contributed a substantial fraction of redox-active trace metals. Abstract : Non-tailpipe emissions (brake wear and resuspension of road dust) are rising, while PM2.5 has markedly decreased mainly due to reduced emissions from fossil fuels.